2014
DOI: 10.1210/jc.2014-1217
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Appraisal of Lactose Intolerance as Cause of Increased Need for Oral Thyroxine

Abstract: These findings show that lactose intolerance significantly increased the need for oral T4 in hypothyroid patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 20 publications
3
59
0
2
Order By: Relevance
“…Numerous published studies have demonstrated the difficulty of maintaining patients in the guideline-recommended therapeutic range for TSH using levothyroxine, with as many as 32-48% of patients being categorized as having either a "subadequate" or "excessive" response to therapy [3,[43][44][45][46]. Factors affecting levothyroxine efficacy include patient persistence and compliance, medication tolerability, Since levothyroxine is an NTI drug, small differences in dose or blood concentration may lead to therapeutic failures or adverse drug reactions [4][5][6][7][8][9]47]. It is not surprising that patients, pharmacists, and physicians have been concerned regarding the use of generic NTI drugs with varying levels of potency [48], particularly in diseases such as hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous published studies have demonstrated the difficulty of maintaining patients in the guideline-recommended therapeutic range for TSH using levothyroxine, with as many as 32-48% of patients being categorized as having either a "subadequate" or "excessive" response to therapy [3,[43][44][45][46]. Factors affecting levothyroxine efficacy include patient persistence and compliance, medication tolerability, Since levothyroxine is an NTI drug, small differences in dose or blood concentration may lead to therapeutic failures or adverse drug reactions [4][5][6][7][8][9]47]. It is not surprising that patients, pharmacists, and physicians have been concerned regarding the use of generic NTI drugs with varying levels of potency [48], particularly in diseases such as hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Levothyroxine is classified as a narrow therapeutic index (NTI) medication, which indicates that small differences in absorption or bioavailability may lead to therapeutic failure or adverse drug reactions [4][5][6][7][8][9]. Currently, levothyroxine medications are available in various formulations, including compressed tablets (generic and branded) and soft gel caps.…”
Section: Introductionmentioning
confidence: 99%
“…Exclusion criteria were: i) a history of hyperthyroidism or toxic nodular goitre as well as the presence of autonomously functioning areas in the thyroid scan; ii) the recent use (!6 months) of drugs known to interfere with thyroid homeostasis (20); iii) the presence of concomitant gastrointestinal disorders (gastritis related to Helicobacter pylori infection, atrophic gastritis, coeliac disease, lactose intolerance, etc.) known to increase L-T 4 requirement (21,22,23); iv) being pregnant.…”
Section: Methodsmentioning
confidence: 99%
“…All patients with NTMG were treated with an individually tailored dose of T 4 , as previously described (21,22,23,24) and in semi-suppressive mode (target serum TSHZ0.1-0.5 mU/l) (2). The individually tailored dose is the dose of T 4 which is administered following a standardized assumption procedure and titrated on the basis of patient's age, weight, BMI, the amount of residual thyroid tissue and the ability to absorb the hormone (12,14,15,21,22,23,24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation